Pengaruh Dosis Probiotik Aquaenzyms Berbeda Pada Pakan Terhadap Pertumbuhan Dan Kelulushidupan Ikan Baung (Hemibagrus nemurus) - Lelinur Indah Damai Yani Nazara Indah Damai Yani Nazara; Mulyadi Mulyadi; Usman MT Usman MT (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on3rd November to7thDecember 2017 in the Laboratory of Aquaculture Technology, Marine and Fisheries Faculty, University of Riau, Pekanbaru. The main purpose of this study was to determine the effect of different aquaenzyms probiotic doses on fish feed toward the growth performance and survival rate of Channel Cafish (Hemibagrus nemurus). The probiotic was used in this study was aquaennzyms probiotic which is composed of Bacillus sp. This research used a completely randomized design (CRD) with one factor, five treatments and three replications. Doses of probiotic were used in this research were P1 (4 g/kg of feed), P2 (4.5 g/kg of feed), P3 (5 g/kg of feed), P4 (5.5g/kg of feed) dan P5 (6 g/kg of feed). The results showed that P1, P2, P3, P4 and P5gavesignificant effect (P<0,05)toward the absolut weightgrowth, absolut length growth and spesific growth rate. While at the feed efficiency, feed conversion ratio and survival rate didn’t give a significant effect on any treatments (P>0.05). The best treatment was on the addition 6 g/kg of feed of probiotic dose by giving the 15.45 g of absolut weigth growth, the absolut length growth was 8.30 g, spesific growth rate was 5.89 g, feed efficiency was 82.98% g, feed conversion ratio was 1.21 and survival rate was 92.4 %. Keyword : Probiotics, Hemibagrus nemurus, Growth